2010
DOI: 10.1007/s00540-009-0858-9
|View full text |Cite
|
Sign up to set email alerts
|

Intrathecal catheterization after unintentional dural puncture during orthopedic surgery

Abstract: Inserting an epidural catheter through the dural tear following an unintentional dural puncture and leaving it in place for 24 h significantly reduces the incidence of PDPH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Second, these patients are at increased risk of developing a PDPH. Although keeping intrathecal catheters in situ for 24 hr was thought to reduce the incidence of PDPH 16 , a recent prospectively controlled trial 14 showed no difference in either the incidence of headache or use of blood patch if intrathecal catheters were maintained for 24 hr.…”
Section: Discussionmentioning
confidence: 99%
“…Second, these patients are at increased risk of developing a PDPH. Although keeping intrathecal catheters in situ for 24 hr was thought to reduce the incidence of PDPH 16 , a recent prospectively controlled trial 14 showed no difference in either the incidence of headache or use of blood patch if intrathecal catheters were maintained for 24 hr.…”
Section: Discussionmentioning
confidence: 99%